173k views
0 votes
Evaluate the expression when b=-2 and y=6 .
b-6y

Evaluate the expression when b=-2 and y=6 . b-6y-example-1
User Fizch
by
5.3k points

2 Answers

1 vote

Answer:

-38

Explanation:

steps:

1:write the question nicely.

2: replace the number given instead of letters.

3: solve according to bedmas rule.so u will solve

-6(6) so it will be = to -36.

4: so -2-36=-38

Evaluate the expression when b=-2 and y=6 . b-6y-example-1
Evaluate the expression when b=-2 and y=6 . b-6y-example-2
Evaluate the expression when b=-2 and y=6 . b-6y-example-3
User MadEqua
by
5.9k points
4 votes

Explanation:

b-6y

if b=-2 and y=2, then

b-6y= (-2)-{6×(2)}

=(-2)-12

=-2-12

=-14

Hence, the value will be -14.

User Zpangwin
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.